Analýza činností vzdělávací a rekvalifikační Agentury N+N s.r.o. - Nováková, Pavlína (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá analýzou vzdělávání v České republice a následně analýzou činností vzdělávací a rekvalifikační Agentury N+N s. r. o. Cílem je vymezit problematiku vzdělávání dospělých v České republice a možnosti jeho rozvoje a komparovat zjištěné poznatky s praxí.

This bachelor work deals with a further education analysis in the Czech Republic and consequently in an analysis of activities of educational and retraining Agency N+N Ltd. The aim of this bachelor work is to determine further education problems and possibilities of its development and to compare the knowledge gained by work experience.
Analysis of activities of educational and retraining agency N+N Ltd.
Keywords: Education; educational institute; retraining scheme; Vzdělávání; vzdělávací společnosti; rekvalifikace